MARKETING STRATEGY OF GHARAR BUSINESS SCHEMES: Mystery Box on E-Commerce Shopee Platform - Nur Rizqi Febriandika; Nabila Putri Tsany; Tipmanee Sriplod (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2022)
ABSTRACT Mystery box sale and purchase have developed into a fraudulent area, the prices and goods obtained are not appropriate, so consumers feel at a loss. This study aims to determine the marketing strategy and sales mechanism of the mystery box. The research method used in this research is descriptive qualitative with the type of research used in this study being observation by examining mystery box products in Shopee. Based on the results of the analysis carried out on the Shopee application, two types of keywords were found. The first keyword is the Mystery Box and the second keyword is the